Minimally invasive rehabilitation with porcelain veneers: case report - Cisneros Boada, Danela (2019)
The present document exposes the aesthetic dental rehabilitation in the anterior dental sector, recovering the characteristics of natural teeth as color and shape, through ceramic veneers and crowns, getting improve the smile in the face of patient. The intervention by minimally invasive procedures as veneers, recover quickly and with minimum error margin the patient's aesthetics, however, an adequate diagnosis, planning processes, listen the patient's needs and prioritize them, constitute the key to success achieved.